Ketone-derived diazo-iodonium salts as reagents for methionine selective functionalization - Goh, Zhang-He; Gaunt, Matt (Synlett)
Selective modification of methionine residues provides a valuable strategy for the site-specific labelling of proteins and peptides. We describe here the synthesis and evaluation of aryl ketone-derived diazo hypervalent iodine reagents as tools for this transformation. These reagents display enhanced reactivity compared to their ester counterparts, enabling efficient modification across a selection of peptide and small protein systems. This was particularly prominent in cases where the methionine residue is buried, such as in ubiquitin, where significant differences in performance were observed between the ketone-and ester-derived reagents. The aryl ketone scaffold allows straightforward incorporation of bioorthogonal handles, facilitating downstream functionalization. These findings broaden the scope of our methionine-directed bioconjugation and highlight opportunities for the development of new chemical biology applications.